2018
DOI: 10.1073/pnas.1803916115
|View full text |Cite
|
Sign up to set email alerts
|

Pupil mimicry promotes trust through the theory-of-mind network

Abstract: The human eye can provide powerful insights into the emotions and intentions of others; however, how pupillary changes influence observers' behavior remains largely unknown. The present fMRI-pupillometry study revealed that when the pupils of interacting partners synchronously dilate, trust is promoted, which suggests that pupil mimicry affiliates people. Here we provide evidence that pupil mimicry modulates trust decisions through the activation of the theory-of-mind network (precuneus, temporo-parietal junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
91
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 69 publications
(108 reference statements)
13
91
3
Order By: Relevance
“…For example, Harrison and colleagues (Harrison et al, 2006) found that pupil contagion, besides brainstem pupillary control nuclei, also recruits other cortical and subcortical regions implicated in social cognition and Theory of Mind (ToM), such as STS, amygdala, frontal operculum and intraparietal sulcus. Moreover, when pupils of interacting partners synchronously dilate, trust decisions are promoted through the activation of ToM network including the precuneus, the temporo-parietal junction (TPJ), STS, and mPFC (Prochazkova et al, 2018). These and other similar data support the contention that pupil size influences the vicarious understanding of expressed emotions and affords an evolutionary ancient neurophysiological mechanism that is active across the primate lineage to promote affiliation, bonding, and trust through mimicry (Carsten et al, 2018;Kret, 2015;Kret and De Dreu, 2017).…”
Section: Neural Bases Of Mimicry and Yawn Contagionmentioning
confidence: 52%
“…For example, Harrison and colleagues (Harrison et al, 2006) found that pupil contagion, besides brainstem pupillary control nuclei, also recruits other cortical and subcortical regions implicated in social cognition and Theory of Mind (ToM), such as STS, amygdala, frontal operculum and intraparietal sulcus. Moreover, when pupils of interacting partners synchronously dilate, trust decisions are promoted through the activation of ToM network including the precuneus, the temporo-parietal junction (TPJ), STS, and mPFC (Prochazkova et al, 2018). These and other similar data support the contention that pupil size influences the vicarious understanding of expressed emotions and affords an evolutionary ancient neurophysiological mechanism that is active across the primate lineage to promote affiliation, bonding, and trust through mimicry (Carsten et al, 2018;Kret, 2015;Kret and De Dreu, 2017).…”
Section: Neural Bases Of Mimicry and Yawn Contagionmentioning
confidence: 52%
“…Importantly, the precuneus, AG and ITG responded to selfinitiated actions to a greater extent in EX compared with FG. These brain regions were commonly engaged during theory of mind and social emotional processing (Prochazkova et al, 2018;Thye, Ammons, Murdaugh, & Kana, 2018;Tsoi, Dungan, Chakroff, & Young, 2018), as well as during self- Fig. 4 Correlation of regional responses to self-agency to behavioral performance.…”
Section: Self-initiated Action: Tossing Versus Catching and Tossing Vmentioning
confidence: 99%
“…During social interactions, humans tend to synchronize on different levels: They mimic postures (Ramseyer & Tschacher, 2011), facial expressions (Chartrand & Bargh, 1999) and align their level of physiological arousal (Feldman, Magori-Cohen, Galili, Singer, & Louzoun, 2011;Levenson & Gottman, 1983;Prochazkova et al, 2018). Although this synchrony comes naturally and without effort, it is a great challenge for social scientists to measure it statistically.…”
Section: Introductionmentioning
confidence: 99%
“…Synchrony is a multifaceted phenomenon evident on the behavioral, physiological, and neural level. Not surprising then, the causes and consequences of synchrony have been studied in a broad range of contexts investigating the dynamic nature of social interactions from clinical (Galazka et al, 2019;Wehebrink, Koelkebeck, Piest, De Dreu, & Kret, 2018), developmental (de Klerk, Hamilton, & Southgate, 2018;Shih, Quiñones-Camacho, Karan, & Davis, 2019), evolutionary (Mancini, Ferrari, & Palagi, 2013;Palagi, Leone, Mancini, & Ferrari, 2009), neural (Hasson, Nir, Levy, Fuhrmann, & Malach, 2004;Prochazkova et al, 2018), social (Behrens et al, 2019;Tarr, Launay, & Dunbar, 2016), and cognitive (Kret, Fischer, & De Dreu, 2015;Kret & De Dreu, 2017) perspectives. Such fascination across disciplines has unraveled the far-reaching scope of synchrony: it has been demonstrated in different species, it occurs from birth on, and it influences a variety of interpersonal processes such as marital quality, cooperative success between strangers and outcomes of therapeutic interactions (Behrens et al, 2019;Feldman et al, 2011;Kret, Tomonaga, & Matsuzawa, 2014;Levenson & Gottman, 1983;Ramseyer & Tschacher, 2011).…”
Section: Introductionmentioning
confidence: 99%